Bt Crops Producing Cry1Ac, Cry2Ab and Cry1F Do Not Harm the Green Lacewing, Chrysoperla rufilabris - Tian, Jun-Ce (Public Library of Science, 2013)

(untitled)
The biological control function provided by natural enemies is regarded as a protection goal that should not be harmed by the application of any new pest management tool. Plants producing Cry proteins from the bacterium, Bacillus thuringiensis (Bt), have become a major tactic for controlling pest Lepidoptera on cotton and maize and risk assessment studies are needed to ensure they do not harm important natural enemies. However, using Cry protein susceptible hosts as prey often compromises such studies. To avoid this problem we utilized pest Lepidoptera, cabbage looper (Trichoplusia ni) and fall armyworm (Spodoptera frugiperda), that were resistant to Cry1Ac produced in Bt broccoli (T. ni), Cry1Ac/Cry2Ab produced in Bt cotton (T. ni), and Cry1F produced in Bt maize (S. frugiperda). Larvae of these species were fed Bt plants or non-Bt plants and then exposed to predaceous larvae of the green lacewing Chrysoperla rufilabris. Fitness parameters (larval survival, development time, fecundity and egg hatch) of C. rufilabris were assessed over two generations. There were no differences in any of the fitness parameters regardless if C. rufilabris consumed prey (T. ni or S. frugiperda) that had consumed Bt or non-Bt plants. Additional studies confirmed that the prey contained bioactive Cry proteins when they were consumed by the predator. These studies confirm that Cry1Ac, Cry2Ab and Cry1F do not pose a hazard to the important predator C. rufilabris. This study also demonstrates the power of using resistant hosts when assessing the risk of genetically modified plants on non-target organisms.